(untitled) (Research, Society and Development, 2022)
Cerrado biodiversity has been threatened by the increase in agricultural production in the state of Tocantins and the increase in the use of pesticides. This work was carried out in the Formoso do Araguaia region, on the banks of the Formoso River, which is home to about 1,825 indigenous people and is one of the largest indigenous lands in the state of Tocantins, Brazil. The presence of pesticides of the imidazolinone and strobirulin classes was verified, analyzed by UHPLC-MS/MS from April 2018 to February 2019, to assess the impacts of these pesticides on the biodiversity of the study site. After the analyses, five active principles (azoxystrobin, phenamidone, imazethapyr, tricyclazole and trifloxystrobin) were detected in the water matrix, two active principles (azoxystrobin and tricyclazole) in the soil matrix, but no active principle was detected in the sediment matrix. Contamination in the region, where riverine and indigenous people use this water for cultivation, hygiene and food, which is worrying, are exposed to these substances.